Pengaruh Pinjaman Online Terhadap Generasi Muda di Era Society - Mastufah, Neneng; Fadzillah, Tri Utami Tasya; Adawiah, Dewi Siti; Mustakim, Usep Saepul (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the impact of online loan services (pinjol) on the community, both in terms of benefits and risks. With the development of financial technology (fintech), online loans are an alternative solution to meet urgent financial needs. Its fast, easy, and no-guarantee process is the main attraction. However, these services also bring negative impacts, such as high interest rates, unethical billing, and potential misuse of personal data. Through a qualitative approach, this study examines user experience, applicable regulations, and the role of the government in supervising online loan services. The results of the study show that although online lending helps improve financial inclusion, consumer protection and digital literacy need to be improved to reduce risks that harm society.